Laminar firing and membrane dynamics in four visual areas exposed to two objects moving to occlusion - Harvey, Michael; Roland, Per E. (Frontiers in Systems Neuroscience, 2013)
It is not known how visual cortical neurons react to several moving objects and how their firing to the motion of one object is affected by neurons firing to another moving object. Here we combine imaging of voltage sensitive dye (VSD) signals, reflecting the population membrane potential from ferret visual areas 17,18,19,and 21, with laminar recordings of multiunit activity, (MUA), when two bars moved towards each other in the visual field, occluded one another, and continued on in opposite directions. Two zones of peak MUA, mapping the bars’ motion, moved towards each other along the area 17/18 border, which in the ferret maps the vertical meridian of the field of view. This was reflected also in the VSD signal, at both the 17/18 border as well as at the 19/21 border with a short delay. After some 125 ms at the area 19/21 border, the VSD signal increased and became elongated in the direction of motion in front of both of the moving representations. This was directly followed by a phase of the signal reversing and travelling back from the 19/21 border towards the 17/18 border, seemingly without respect for retinotopic boundaries, where it arrived at 150 ms after stimulus onset. At this point the VSD signal in front of the moving bar representations along the 17/18 border also increased and became elongated in the direction of object motion; the signal now being the linear sum of what has been observed in response to single moving bars. When the neuronal populations representing the bars were some 600 μm apart on the cortex, the dye signal and laminar MUA decreased strongly, with the MUA scaling to that of a single bar during occlusion. Despite a short rebound of the dye signal and MUA, the MUA after the occlusion was significantly depressed. The interactions between the neuronal populations mapping the bars' position, and the neurons in between these populations were, apart from the 19/21 – 17/18 interaction, mainly lateral-horizontal; first excitatory and indu